MEMS based fiber optical microendoscopes - Qiu, Zhen; Piyawattanametha, Wibool (My University, 2015)
Fiber-optical microendoscopy has recently been an essential medical diagnostic tool for patients in investigating tissues in vivo due to affordable cost, high quality imaging performance, compact size, high-speed imaging, and flexible movement. Microelectromechanical systems (MEMS) scanner technology has been playing a key role in shaping the miniaturization and enabling high-speed imaging of fiber-optical microendoscopy for over 20 years. In this article, both review of MEMS based fiber-optical microendoscopy for optical coherence tomography, confocal, and two-photon imaging will be discussed. These advanced optical endoscopic imaging modalities provide cellular and molecular features with deep tissue penetration enabling guided resections and early cancer assessment.
Keywords: Confocal; Fluorescence imaging; MEMS scanner; OCT; Two-photon